Retrieval Practices Enhance Computational and Scientific Thinking Skills - Yaşar, Osman; Maliekal, Jose; Veronesi, Peter; Little, Leigh; Meise, Michael; Yeter, Ibrahim H. (Frontiers in Psychology, 2022)
The notion of computational thinking (CT) as a fundamental competency seems to have inspired many educators and researchers worldwide. A great deal of efforts has been invested in describing CT, its cognitive essence, and manifestations in different fields and ways to teach it at different levels of education. There are plenty of tools available for teaching various CT skills. However, the discourse on what CT means to different stakeholders continues to this date. Some have suggested to categorize it as CT for beginners and CT for professionals. The same argument applies to teaching scientific thinking (ST) skills. Basically, teaching experts’ habits of mind to novices is inherently problematic because of prerequisite content knowledge and practice skills needed to engage in the same thinking processes, not to mention the cost of providing them a similar environment to conduct inquiry and design. A remedy has been suggested to narrow CT and ST skillsets down to core cognitive competencies so they can be introduced in elementary grades and continue to be nurtured during secondary school years. Using a computational approach to cognition (via distributive storage and associative retrieval of information), neuroscientists now see a strong link between the acts of information storage/retrieval and the act of thinking. Not surprisingly, years of research on retrieval practices have shown that they promote not only retention but also inductive and deductive reasoning skills; many of which are core elements of both CT and ST skillsets. We present a retrieval framework based on information processing by a computational mind, description of a related professional development program to educate secondary school teachers (n=275), and the impact of teaching and learning STEM and CT concepts. A survey of teachers showed that the majority (96%) of respondents (n=232) reported a good understanding of CT and retrieval strategies, and how relevant ideas can be implemented and tested in the classroom. A large number of action research studies by teachers (n=122) showed that students who learned STEM and CS concepts through retrieval practices scored 5-30% higher than those using the blocked practice. In most cases, the difference was statistically significant (p <0.05).